Effect of the vitality of the overdenture abutment tooth on stability of the tooth - Khalid Ahmad Omar Arafa (Wolters Kluwer Medknow Publications, 2016)
Objective: This study aimed to examine the effect of overdenture over vital and nonvital abutment teeth on teeth stability (teeth mobility and attachment loss). Materials and Methods: An experimental, parallel design was used and the study was conducted over a 12-month period (December 2013 to November 2014). Thirty patients who voluntarily opted to participate in this study were recruited; the first group received overdenture over vital abutment teeth while the second group received overdenture over nonvital abutment teeth. Attachment loss and teeth mobility were periodically evaluated after 3 months, 6 months, and 12 months. The data were then analyzed by a computerized method [Statistical Package for Social Sciences (SPSS) version 20]. Results: Overdenture over vital abutment teeth showed lower attachment loss and teeth mobility, compared to the overdenture over nonvital abutment teeth. These differences were statistically significant. Conclusion: It was concluded that the overdenture over vital abutment teeth was more stable, with a lower incidence of tooth mobility and less attachment loss than overdentures placed on nonvital teeth.